Effects of salinity (NaCl) on the content photosynthetic pigments in barley varieties (Hordeum vulgare L.) (Experimental biology, 2015)
Barley varieties contrasting in their tolerance (according to preliminary results) to salinity (Asem, Sault, Odesskaya - 100) were taken to study the content of photosynthetic pigments in saline conditions. With increasing concentration of NaCl decreased concentration of chlorophyll a and b, and carotenoids. In tolerant varieties Asem and Saule content of photosynthetic pigments in saline conditions was higher than in non-resistant variety Odesskaya-100. Photosynthetic pigments content directly affects the rate of photosynthesis, which directly influence on crop yields. Contents of photosynthetic pigments are an integral indicator of plant resistance to adverse environmental conditions.
Keywords: barley; salinity; chlorophyll; carotenoids; tolerance